Peranan Self Regulated Learning Terhadap Student Engagement Siswa Kelas XI SMKN Y Palu - Munawarah Munawarah; Nur Akmal; Andi Halima (CV. ULIL ALBAB CORP, 2024)
High-quality education is critical to the successful realization of national goals. Student engagement refers to how students participate and are involved in learning activities both inside and outside the classroom. Self-regulated learning is one of the factors that students must have to influence student engagement. This research aims to determine the role of self-regulated learning on student engagement of class XI students at SMKN Y Palu. This research uses quantitative methods. The respondents in this study were 303 students at SMKN Y Palu who were in grade XI. Data collection techniques use questionnaires. The results of data analysis show that there is a role between self-regulated learning and student engagement. The hypothesis test in this study used simple regression analysis and the results of the hypothesis test showed that the influence of the self-regulated learning variable on student engagement was 26%, while the remaining 74% was influenced by other factors not involved in this research. The implication of this research is that this research is expected to make a positive contribution, especially in psychology and schools, as well as provide additional information related to self-regulated learning and student engagement variables.